(3GdKhQI GdeYdheGJjI h GdJcfhdhLjI h SjGSGJ GdJfejIs - (3ShRGf(B, (3ehRjs ((3HjQhJ(B:s (3OGQ Gdefgd GddHfGfj(B,s, 2009)
(3GdaLhI GdQbejI h JCKjQGJgG aj hGbY GdfXGe GdGbJUGOj GdOhdj, eDTQGJ h JMOjGJ GdaLhI GdQbejI , GdJOGYjGJ GdGbJUGOjI ddaLhI GdQbejI, Hjf GbJUGO GdeYQaI h eLJeY GdeYdheGJ , GdeHGOQGJ GdYGdejI dQOe GdaLhI GdQbejI, CHYGO GdKhQI GdJbfjI GdeYGUQI GdJj JVe GdHYO GdCefj h GdKbGaj, GdHYO GdGbJUGOj, GdHYO GdGLJeGYj h GdCNdGbj, OhQ GdbGfhf GdOhdj aj VHW JOGYjGJ GdKhQI GdJbfjI, MUGfI Mbhb GdGdfSGf aj GdYUQ GdQbej, GOGQI GdGfJQfjJ h GdbeI GdYGdejI deLJeY GdeYdheGJ, eSGYj GddLfI GdGbJUGOjI h GdGLJeGYjI dZQHj BSjG, GYOGO GdOQGSGJ h GdhKGFb, YbO GdeDJeQGJ h GdGLJeGYGJ hhQT GdYed, EUOGQ fTQI JcfhdhLjG GdeYdheGJ h GdGJUGdGJ, fTQ GdJbGQjQ GdSfhjI, GdHfjI GdCSGSjI dJcfhdhLjG GdeYdheGJ h GdGJUGdGJ aj Ohd GdGSch, GdJWHjbGJ GdJcfhdhLjG h SjGSGJ GdJfejI GdeSJOGeI aj eLGd GdJfejI GdGLJeGYjI, aj eLGd GdJfejI GdGbJUGOjI h aj eLGd GdGUdGM GdGOGQj h GdMce GdQTjOs
(3eQGLY U(B.150(3; edGMb U(B.158s
Keywords: (3GdJcfhdhLjG(B- (3NOeGJ GdeYdheGJs; (3GdJfejIs